2001
DOI: 10.1042/bj3590605
|View full text |Cite
|
Sign up to set email alerts
|

Bile-salt hydrophobicity is a key factor regulating rat liver plasma-membrane communication: relation to bilayer structure, fluidity and transporter expression and function

Abstract: Bile-salt hydrophobicity regulates biliary phospholipid secretion and subselection. The aim of this study was to determine whether bile salts can influence liver plasma membrane phospholipids and fluidity in relation to the ATP-dependent transporter. Rats were depleted of bile salts by overnight biliary diversion and then sodium taurocholate was infused intravenously at a constant rate (200nmol/min per 100g of body weight), followed by infusion of bile salts with various hydrophobicities (taurochenodeoxycholat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Introduction of 3a-azides (15, 26) (i.e., with retention of configuration) was accomplished by generating first the b-bromides (39,42). The b-azides (16,27) could be obtained by direct SN2 substitution on the a-mesylates (40,43). Similarly, the 7-b azido analog of UDCA (34) was generated by treating the appropriately protected CDCA-derived mesylate (45) with NaN 3 in DMPU followed by deprotection in aqueous base.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction of 3a-azides (15, 26) (i.e., with retention of configuration) was accomplished by generating first the b-bromides (39,42). The b-azides (16,27) could be obtained by direct SN2 substitution on the a-mesylates (40,43). Similarly, the 7-b azido analog of UDCA (34) was generated by treating the appropriately protected CDCA-derived mesylate (45) with NaN 3 in DMPU followed by deprotection in aqueous base.…”
Section: Synthesismentioning
confidence: 99%
“…1). Notably, eight of these retained an ionizable side chain (7)(8)(9)(15)(16)(17)(18)(19). For comparison, seven DCA analogs were assembled along with LagoDCA (28) the epimeric 12-bOH compound (Fig.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The unexpected up-regulation of bile acid transporters Slc10a2 and Ostb that we found in the present study can be explained by the relative increase of hydrophilic bile acids in the intestinal lumen on the HCa diet, as Ca predominantly precipitates hydrophobic bile acids (24) . Asamoto et al (25) previously found that hydrophilic bile acids are associated with an induction of bile acid transporters. The up-regulation of Slc10a2 and Ostb also implies that the Cainduced increase in faecal excretion of bile acids does not necessarily lead to a reduced enterohepatic circulation (26) and a consequent reduction in energy expenditure (13) .…”
Section: Discussionmentioning
confidence: 95%
“…2). Such a translocation of ABCB11 is associated with a proportion of net bile salt hydrophobicity [13]. In the long term, the enterohepatic circulation of bile salts is controlled by the regulated gene transcription of the liver X receptor alpha (LXRa) and the farnesoid X receptor (FXR) [14] (Fig.…”
Section: Molecular Mechanisms Of Hepatic Bile Salt Metabolismmentioning
confidence: 99%